Gold Mining and Proto-Urbanization : Recent Evidence from Ghana - Fafchamps, Marcel; Koelle, Michael; Shilpi, Forhad (World Bank, Washington, DC, 2015)
Central place theory predicts that agglomeration can arise from external shocks. This paper investigates whether gold mining is a catalyst for proto-urbanization in rural Ghana. Using cross-sectional data, the analysis finds that locations within 10 kilometers from gold mines have more night light and proportionally higher employment in industry and services and in the wage sector. Non-farm employment decreases at 20–30 kilometers distance to gold mines. These findings are consistent with agglomeration effects that induce non-farm activities to coalesce in one particular location. This paper finds that, over time, an increase in gold production is associated with more wage employment and apprenticeship, and fewer people employed in private informal enterprises. It also finds that the changes arising from increasing gold production are not reversed when large gold mines shrink. However this pattern cannot be ascribed unambiguously to agglomeration effects, given an increase in informal mining after formal mines decrease output is also observed.